A History of Dry Needling. Issue 3 (September 2014) - Legge, David
Abstract Objectives: To trace the development of the practice and theoretical basis of dry needling by means of an examination of the literature. Findings: The term dry needling arose from the need to provide a contrast to the injection of a fluid through a hypodermic syringe [now sometimes referred to as wet needling]. Dry needling does not involve the injection of any substance, merely the insertion of a needle. The history of dry needling is inextricably bound up with the search for effective treatment of painful musculoskeletal disorders. In particular, it was the research into the use of injections, to both cause and relieve pain in muscular tissue, that led to the development of trigger point theory and then to the use of dry needling as a treatment. Conclusions: A search of the literature reveals that the important clinical finding that simple dry needling of tender points could produce profound and long-lasting relief of musculoskeletal pain had been published in 1941 and again in 1947. This provoked little interest in the wider academic or clinical community until the focus on acupuncture in the 1970s and the publication of a scientific explanation of the nature of myofascial trigger points in the 1970s and 1980s. Since 2000, there has been a surge in academic interest in dry needling and its use has expanded into the allied health professions of physiotherapy, osteopathy, and chiropractic.